2020
DOI: 10.3389/fonc.2020.562504
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Androgen Receptor Splice Variant 7 in the Treatment of Metastatic Castration-Resistant Prostate Cancer: A Systematic Review and Meta-Analysis

Abstract: BackgroundThe prognostic value of androgen receptor splice variant 7 (AR-V7) for the treatment response of metastatic castration-resistant prostate cancer (mCRPC) remains unclear. In this study, we aimed to synthesize relevant studies that assessed the prognostic value of AR-V7 status for the treatment response of mCRPC patients treated with androgen receptor signalling inhibitors (ARSis) and chemotherapy.MethodsWe searched the PubMed, Embase, and MEDLINE databases by using the keywords AR-V7 and prostate canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…This suggested that ARv7 might be involved in the cross-resistance between ENZ and ABI. Although ARv7-positive patients showed much worse treatment responses to NHT (Armstrong et al, 2020;Wang et al, 2020a;Wang et al, 2020b), the clinical data analysis demonstrated that these patients could significantly benefit from taxane chemotherapy, which was possibly related to the higher activity of the E2F1/AR3 feed-forward loop (Xu et al, 2020). The CXCR7-JAK2/STAT1 signaling pathway, as an independent AR bypass pathway, may also participate in resistance to androgen target therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that ARv7 might be involved in the cross-resistance between ENZ and ABI. Although ARv7-positive patients showed much worse treatment responses to NHT (Armstrong et al, 2020;Wang et al, 2020a;Wang et al, 2020b), the clinical data analysis demonstrated that these patients could significantly benefit from taxane chemotherapy, which was possibly related to the higher activity of the E2F1/AR3 feed-forward loop (Xu et al, 2020). The CXCR7-JAK2/STAT1 signaling pathway, as an independent AR bypass pathway, may also participate in resistance to androgen target therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the exosome-RNA and CTC isolated by plasma samples could be used to detect the androgen receptor splicing variant 7 (AR-V7), a predictive variant of resistance to AR signaling inhibitors. Furthermore, Tagawa and coworkers showed that the absence of the same variants in mCRPC CTC patients may be associated with better taxane treatment outcomes [111][112][113]. In addition, liquid biopsy could be also used to predict resistance to PARP inhibitors (PARPi), which are approved for treatment or maintenance therapy for several malignancies, including PCa.…”
Section: The Role Of Liquid Biopsy In Follow-upmentioning
confidence: 99%
“…The concurrent systematic reviews recently published in Frontiers in Oncology by Zhize Wang et al (1) and Jiaxin Wang et al (2) provide a very similar report on the prognostic value of the androgen receptor splice variant 7 (AR-V7) in castration-resistant prostate cancer. As these might appear, at first glance, to be nearly identical, we believed it was pertinent to herein highlight the differences and summarize the findings.…”
Section: Introductionmentioning
confidence: 93%